Assessment of the anti-bacterial and antioxidant activity of silver nanoparticles produced by oil field reservoirs bacterium - Alshami, Hasan G. A.; Hateet, Rashid R.; Al-Tamimi, Wijdan H. (Scientific Journal of Medical Research, 2023)
Objective: This study aimed to synthesize, characterize, and evaluate the anti-bacterial and antioxidant activity of silver nanoparticles (AgNPs) synthesized using the supernatant of Bacillus cereus strain DBA1.1 isolated from an oil field reservoir. Methods: The Uv-visible (Uv-vis) spectrophotometer, X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), atomic force microscopy (AFM), and zeta potential analysis were used to characterize the synthesized AgNPs. By utilizing the agar well diffusion technique, the anti-bacterial efficacy of AgNPs was assessed against multidrug-resistant (MDR) bacteria isolated from human urinary tract infections (UTI). The antioxidant activity of AgNPs was investigated using the 1,1-diphenyl-2-pyridylhydrazine (DPPH) test. Results: The results indicate the formation of AgNPs through the visual observations of dark brown color, which UV absorption at 432 nm further confirms this. The fabricated AgNPs had a spherical shape, and the average size was found to be 20.83, 17.47, and 18.11 nm according to XRD analyses, TEM, and SEM, respectively. In AFM, AgNPs were measured to have a mean diameter of about 65 nm. The mean negative zeta potential of AgNPs was -14.5 mV. AgNPs demonstrated significant anti-bacterial properties against MDR bacteria depending on concentration, with the highest diameter inhibition zone of 24.33 ± 0.57 mm against Staphylococcus haemolyticus at a concentration of 1000?g/mL. Powerful antioxidant activity was noticed, with an IC50 value of 112.16 ?g/mL. Conclusions: The present work concluded that synthesized AgNPs were spherical, monodisperse, stable, and within acceptable sizes. They may be good candidates for further biological applications.